Professionals : magnates, entrepreneurs, career women - Hanson, Jillian (Austin, TX : Raintree Steck-Vaughn, 2000)
Presents brief profiles of women who have been successful in the business world, from Madame Alexander and Linda Alvarado to Sarah Breedlove Walker and Barbara Walters.
Includes index.
Keywords: Women in the professions -- Biography -- Juvenile literature; Women executives -- Biography -- Juvenile literature; Businesswomen -- Biography -- Juvenile literature; Women in the professions; Businesspeople; Women -- Biography